2002
DOI: 10.1124/jpet.102.040105
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Allergic Dermal Inflammation by the Novel Imidazopyridazine Derivative TAK-427 in a Guinea Pig Experimental Model of Eczema

Abstract: Antigen challenge by patch ovalbumin emulsion induced an eczema-like skin lesion in epicutaneously sensitized guinea pigs. Diseased skin sites were macroscopically characterized by manifestations of dermatitis, such as erythema, edema, and papules, and microscopically characterized by acanthosis, spongiosis, and dermal infiltration by eosinophils. Using such lesions as a model of eczema, we evaluated the potential value of as a therapeutic agent for atopic dermatitis by comparing it with dexamethasone and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…Keratinocytes at the site of CD overexpress numerous cytokines and chemokines, such as TNF-α, IFN-γ, MCP-1 and IL-10 (17-19). It has been previously reported that IFN-γ is important in the development of skin hypertrophy, and TNF-α and MCP-1 function as stimulants of immune cell recruitment around blood vessels (17)(18)(19). In the present study, the topical application of MEKS inhibited the histopathological features of CD via suppression of TNF-α, IFN-γ and MCP-1 expression.…”
supporting
confidence: 59%
“…Keratinocytes at the site of CD overexpress numerous cytokines and chemokines, such as TNF-α, IFN-γ, MCP-1 and IL-10 (17-19). It has been previously reported that IFN-γ is important in the development of skin hypertrophy, and TNF-α and MCP-1 function as stimulants of immune cell recruitment around blood vessels (17)(18)(19). In the present study, the topical application of MEKS inhibited the histopathological features of CD via suppression of TNF-α, IFN-γ and MCP-1 expression.…”
supporting
confidence: 59%
“…NOD2/TLR2 ligand treatment alone did not induce effects in the absence of MC903 (Figure 1a-e and g and h), suggesting that the deteriorating effects of the NOD2/TLR2 ligands might only occur in pre-established skin lesions wherein the epidermal barrier function is disturbed. Previous publications have shown that eosinophil infiltration might only be observed in the dermal layer of AD skin lesions; 24,29 however, here we found that topical S. aureus-associated NOD2/TLR2 ligands led to further epidermal infiltration of eosinophils in our mouse model of AD-like skin inflammation induced by MC903 (Figure 1f). …”
Section: Topical Application Of Nod2/tlr2 Ligands Induced Exacerbatiocontrasting
confidence: 42%
“…-yl]-2-methylpropionic acid dihydrate (TAK-427) was developed as a therapeutic agent for atopic dermatitis [6]. In an in vitro pharmacokinetic study, the transport of TAK-427 across Caco-2 cells was in a predominantly secretory direction suggesting that TAK-427 could be a substrate for P-gp.…”
Section: -[6-[[3-[4-(diphenylmethoxy)piperidino]propyl]amino]imidazomentioning
confidence: 99%